"My other hand": The central role of smartphones and SNSs in Korean students' lives and studies. (January 2023) - Webster, Thomas E.; Paquette, Jean
Abstract: Numerous studies have shown specific benefits of smartphones and social network sites (SNSs) for entertainment, connection, education, and even research, while an equal number have focused on concerns about overuse, negative academic outcomes, and mental health issues. However, few studies to date have taken a more holistic view of how smartphones and SNSs affect the lived experiences of students in and out of the classroom in order to aid teachers in deciding how to address them in their teaching. The current study builds upon an earlier study on teachers' perceptions and uses of technology in Korea in which findings indicated that teacher decision making was increasingly contingent upon determining the role of smartphones in students' learning and lives. An exploratory mixed methods grounded theory approach was adopted involving semi-structured interviews and a survey questionnaire at one American and three Korean universities. Findings formed a central category entitled "my other hand" that frames the all-encompassing role that smartphones play in students' academic and personal lives. Clear indications of extended mind cognition were found highlighting teachers' need to better understand how student lives and perspectives toward learning are evolving including the increasing role of YouTube as an informal classroom supplement. Implications suggest that given the profound nature of smartphones and SNSs in students' lives, gaps between institutional teaching and learning and ways of being in the new "metacognitive economy" will become exacerbated unless properly addressed. Highlights: Smartphones have profoundly changed students' physical and thinking abilities. Extended mind cognition is apparent in student smartphone use. YouTube is used to supplement perceived shortcomings in classroom lessons. Need for teachers to address the new "metacognitive economy".